Effects of Central Obesity on Esophageal Epithelial Barrier Function. (22nd July 2021) - Gibbens, Ying Y.; Lansing, Ramona; Johnson, Michele L.; Blevins, Christopher H.; Katzka, David A.; Iyer, Prasad G.
Abstract : INTRODUCTION: We assessed if obesity perturbs the esophageal epithelial barrier function independent of promotion of gastroesophageal reflux (GER). METHODS: Thirty-eight participants were divided into 4 groups: Obesity−/GER–, Obesity+/GER−, Obesity−/GER+, and Obesity+/GER+. Esophageal intercellular space and desmosome density (structural integrity) and fluorescein leak (functional integrity) were measured. RESULTS: The Obesity+/GER− group demonstrated increased intercellular space, reduced desmosome density, and increased fluorescein leak compared with control subjects. These changes were similar but not additive to findings seen in Obesity−/GER + and Obesity+/GER+ patients. DISCUSSION: Central obesity impairs structural and functional integrity of the esophageal barrier independent of GER, likely predisposing to esophageal injury.